High-quality 100% Ce3+:(Lu1−xYx)2SiO5 single crystals grown by the hydrothermal technique - Encarnación G. Víllora; Makoto Saito; Kiyoshi Shimamura (Applied Physics Express)
The growth of Ce:(Lu _1−x Y _x ) _2 SiO _5 single crystals by the hydrothermal technique is demonstrated. Crystallographic defects are suppressed thanks to the growth at much lower temperatures, and therefore, the complete incorporation of cerium in the Ce ^3+ valence state is obtained. The growth under supercritical water lowers the temperature to less than half the melting point. In contrast, crystals grown from melt by the standard Czochralski technique possess intrinsic defects and undesirable Ce ^4+ ions as charge compensators. The growth of large-size single crystals with improved scintillation properties at a low cost is envisaged.